Strategic Management of Character Development to Enhance Creativity Among Junior High School Students - Saadul Latifah; Eka Diana (Fitrah, 2026)
This study focus upon examining strategic management applied within formation concerning student character value, alongside hope concerning fostering their creativity. Essential, this study aim to identify effective method for building student character that can help enhance their creative ability within school environment. This particularly important because, within today’s era concerning globalization, student creativity remain key to preparing innovative younger generation capable concerning competing at global level. Research method employed were qualitative, utilizing case study at junior high school that have implemented character development program regular plus systematic. Research result indicate that character development involving daily habit, project-based learning, plus extracurricular activity have significant impact upon enhancing student creativity. Based upon this finding, it recommended that school incorporate character development into curriculum upon regular basis plus involve various stakeholder to create more organized program that better support student creativity.